Characteristics of interventions targeting multiple lifestyle risk behaviours in adult populations: a systematic scoping review. - Kristel King; Nick Meader; Kath Wright; Hilary Graham; Christine Power; Mark Petticrew; Martin White; Amanda J Sowden (PLoS ONE)
Background Modifiable lifestyle risk behaviours such as smoking, unhealthy diet, physical inactivity and alcohol misuse are the leading causes of major, non-communicable diseases worldwide. It is increasingly being recognised that interventions which target more than one risk behaviour may be an effective and efficient way of improving people's lifestyles. To date, there has been no attempt to summarise the global evidence base for interventions targeting multiple risk behaviours. Objective To identify and map the characteristics of studies evaluating multiple risk behaviour change interventions targeted at adult populations in any country. Methods Seven bibliographic databases were searched between January, 1990, and January/ May, 2013. Authors of protocols, conference abstracts, and other relevant articles were contacted. Study characteristics were extracted and inputted into Eppi-Reviewer 4. Results In total, 220 studies were included in the scoping review. Most were randomised controlled trials (62%) conducted in the United States (49%), and targeted diet and physical activity (56%) in people from general populations (14%) or subgroups of general populations (45%). Very few studies had been conducted in the Middle East (2%), Africa (0.5%), or South America (0.5%). There was also a scarcity of studies conducted among young adults (1%), or racial and minority ethnic populations (4%) worldwide. Conclusions Research is required to investigate the interrelationships of lifestyle risk behaviours in varying cultural contexts around the world. Cross-cultural development and evaluation of multiple risk behaviour change interventions is also needed, particularly in populations of young adults and racial and minority ethnic populations.